An Intrinsic Algorithm for Viewing Angle Tolerance of Object Discrimination in Human Subjects - Okamura, Jun-ya; Oshima, Jin; Yamaguchi, Reona; Yamashita, Wakayo; Wang, Gang (Canadian journal of experimental psychology, 2020)
Prevailing theories suggest that view-invariant object recognition is accomplished via spatiotemporal correlations of multiple views that bind different views to the same object. However, it is unknown how the exposure to multiple views without association affects view-invariant recognition generating. Behavioural studies have shown that monkeys acquired view-invariant object recognition capability in a range of the viewing angles of 30° to 60° after experiencing discrimination of similar objects at each of several viewing angles without associating different views, but the monkeys could not discriminate novel objects from similar distractors when the viewing angle changed. In the present study the development of the view invariance was tested in the human subjects and compared with the results of the monkeys previously reported. The view-invariant object recognition capability of human subjects was tested using either familiar objects that the subjects experienced in a preparatory object discrimination task at the same viewpoints or novel objects that the subjects had never experienced. In the viewing angle range of 30°, human subjects showed significant object discrimination capability across views, with no need for prior experience of the objects. Prior discrimination experience within the same viewpoints endowed the human subjects with broadening of the viewing angle tuning, because an object discrimination test immediately after the prior discrimination experience at a single view showed wider viewing angle tuning than a test without prior experience. Les théories actuelles suggèrent que la reconnaissance d'objets invariante au point de vue se réalise à l'aide de corrélations spatio-temporelles de vues multiples qui lient les différentes vues au même objet. Or, on ne sait pas comment l'exposition à de multiples points de vue sans association affecte la génération de la reconnaissance invariante au point de vue. Les études comportementales ont montré que les singes acquièrent la capacité de reconnaissance d'objets invariante au point de vue dans une gamme d'angles de vue de 30° à 60° après avoir expérimenté la discrimination d'objets similaires à chacun des angles de vue sans associer différents points de vue, mais les singes n'arrivaient pas à discriminer de nouveaux objets de distractions similaires lorsque l'angle de vue changeait. Dans la présente étude, le développement de l'invariance au point de vue a été testée sur des sujets humains et comparée avec les résultats des singes, présentés antérieurement. La capacité de reconnaissance d'objets invariante au point de vue de sujets humains a été testée à l'aide d'objets familiers que les sujets expérimentaient au cours d'une tâche de discrimination d'objet préparatoire aux mêmes points de vue ou nouveaux objets que les sujets n'avaient jamais expérimenté. Dans la gamme d'angles de vue de 30°, les sujets humains ont montré des capacités de discrimination d'objet significatives à travers les différents points de vue, sans avoir besoin d'une expérience préalable des objets. Une expérience de discrimination préalable des mêmes points de vue procurait aux sujets humains une gamme d'angles de vue élargie, puisqu'un test de discrimination d'objets administré tout de suite après l'expérience de discrimination antérieure à un seul point de vue a révélé une gamme d'angles de vue plus large sans expérience préalable. Public Significance Statement Prevailing theories suggest that spatiotemporal correlation of different views of an object was required to develop the view-invariant object recognition capability. However, monkey subjects acquired the view-invariant object recognition capability in a range of viewing angles of up to 60° after preparatory experience of the object images at each of several viewing angles. Human subjects acquired view-invariant object recognition capability in a viewing angle range of at least 30° even without the prior experiences, and discrimination experience between similar objects at only one view generated wider viewing angle tuning than without the discrimination experience.